Influence of regional variations in ocean characteristics and trophic relationships on cadmium accumulation in Antarctic pelagic and benthic organisms - Roberto Bargagli; Emilia Rota (Ukrainian Antarctic Journal, 2025)
Cadmium (Cd) concentrations in Antarctic marine organisms are much higher than expected for such a remote, pristine environment. Bioaccumulation is principally due to water circulation and upwelling, as well as the nutrient-like behaviour of Cd in areas of high primary productivity. The low availability of zinc (Zn) and other trace elements favours Cd use by diatoms as a cofactor in carbon anhydrase, and the metal is also highly concentrated by small autotrophs and heterotrophs that develop a high surface-to-volume ratio. Thus, in pelagic food webs, grazing micro- and mesozooplankton, as well as the juvenile stages of Antarctic krill with a small oral apparatus, accumulate high concentrations of Cd and transfer the metal to amphipods and other secondary consumers. In coastal marine ecosystems with high primary productivity, such as those bordering the Ross Sea, a large amount of phytoplankton sinks in the summer, contributing to Cd accumulation in benthic invertebrates. Total body Cd concentrations are lower in benthic and pelagic fish, seabirds, and marine mammals than in many invertebrate species. Seabirds that feed on amphipods and other crustaceans smaller than Antarctic krill accumulate higher amounts of Cd. Comparisons of Cd content in representative benthic invertebrate species, fish, and penguins from coastal marine ecosystems at King George Island and Terra Nova Bay (Ross Sea) indicate much higher bioaccumulation in the latter area. This is likely due to enhanced upwelling of seawater, high concentrations of soluble Cd in surface waters, notable algal blooms in spring and summer, and the involvement of invertebrate taxa other than Antarctic krill in transferring energy and metals along pelagic food webs.